Pengaruh Corporate Social Responsibility dan Good Corporate Governance terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Moderasi pada Sektor Pertambangan Periode 2016-2019 - Darson Simon Simamora; Atik Djajanti (Sekolah Pascasarjana Perbanas Jakarta, 2022)
This study aims to analyze the effect of CSR and GCG on the value of the mining sector company and financial performance of the moderating variable. The data used in this study is secondary data from the IDX with a sample of 19 mining sector companies during the period 2016 – 2019. Data processing and testing techniques use the SEM concept with the Partial Least Square method using smart PLS 3.0 software. The results of the study state that CSR has an effect on firm value and ROA is able to strengthen the relationship between CSR and firm value. GCG as proxied by the number of the board of directors has no effect on firm value and ROA has no effect on the relationship between GCG and firm value. These results indicate that the more CSR disclosures made by the company, the better the company's image, but GCG through the number of boards of directors has not been able to improve the company's image in the eyes of the public.